Polymer solid electrolyte and preparation method thereof
By utilizing the crosslinking structure of crosslinkable functional groups with lithium salts and solvents in polymer solid electrolytes, combined with the freezing and thawing process, amorphous polymer chains are formed, and the problem of low lithium ion mobility in the prior art is solved and improved The conductivity is simplified and the preparation process is simplified.
Patent Information
- Application Number
- CN202380042312.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-05-31
- Filing Date
- 2023-05-31
- Publication Date
- 2025-01-03
AI Technical Summary
In the high crystallinity of existing polymer solid electrolytes in high temperature drying process, the lithium ion mobility is low, making it difficult to improve ion conductivity, and the dispersion and compatibility after increasing the plasticizer are difficult to ensure, which affects the preparation process.
Using a combination of a polymer containing crosslinkable functional groups with lithium salts and different solvents, a crosslinked structure is formed through the freezing and thawing process to prevent the increase of crystallinity, and to increase the conductivity through solvent exchange to form an amorphous polymer chain to improve lithium ion mobility.
It is achieved to reduce the crystallinity of the polymer solid electrolyte, improve its ionic conductivity, enhance brittleness and ductility, and simplify process conditions without the need for plasticizers.
Smart Images

Figure BDA0005148149280000151 
Figure BDA0005148149280000171 
Figure BDA0005148149280000181
Abstract
Description
Technical Field
[0001] This application claims priority based on Korean Patent Application No. 10-2022-0066984 filed on May 31, 2022 and Korean Patent Application No. 10-2023-0070168 filed on May 31, 2023, the entire contents of which are incorporated as part of this specification.
[0002] The invention relates to a polymer solid electrolyte and a preparation method thereof. Background Art
[0003] Since lithium secondary batteries using liquid electrolytes have a structure in which the negative electrode and the positive electrode are separated by a separator, if the separator is damaged by deformation or external impact, a short circuit may occur, which may lead to dangers such as overheating or explosion. Therefore, it can be said that the development of a solid electrolyte that can ensure safety in the field of lithium secondary batteries is a very important task.
[0004] Lithium secondary batteries using solid electrolytes have the advantages of improving battery safety, preventing electrolyte solution leakage, improving battery reliability, and being easy to manufacture thin batteries. In addition, since lithium metal can be used as a negative electrode, energy density can be increased, and in addition to small secondary batteries, it is expected to be applied to high-capacity secondary batteries for electric vehicles, and is attracting attention as a next-generation battery.
[0005] In solid electrolytes, as raw materials of polymer solid electrolytes, polymer materials having ion conductivity can be used, and hybrid materials in which polymer materials and inorganic materials are mixed are also proposed. As inorganic materials, inorganic materials such as oxides or sulfides can be used.
[0006] This conventional polymer solid electrolyte is prepared by a high temperature drying process after forming a coating film. However, the conventional preparation technology of polymer solid electrolytes is limited in that it is difficult to prepare a polymer solid electrolyte with improved ionic conductivity due to the high crystallinity of crystalline polymers or semi-crystalline polymers. In other words, the higher the crystallinity of the polymer, the lower the mobility of the polymer chain. Therefore, since the movement of lithium ions inside the polymer solid electrolyte is restricted, it is difficult to improve the ionic conductivity of the polymer solid electrolyte.
[0007] For example, conventional polymer solid electrolytes can be prepared by using polyvinyl alcohol (PVA) containing hydroxyl groups as crosslinkable functional groups as a polymer to form a coating film, and then performing a high temperature drying process. Specifically, PVA is dissolved in water to prepare a PVA aqueous solution, and then the PVA aqueous solution is coated on a substrate by solution casting to form a coating film, and dried at room temperature or high temperature to form a polymer solid electrolyte in the form of a PVA film. At this time, high temperature can refer to 80 ° C (which is the glass transition temperature (Tg) of PVA) or above. During the drying process, after the water evaporates, hydrogen bonds between the crosslinkable functional groups contained in the PVA are formed, and polymer chain folding occurs due to hydrogen bonds, so the crystallinity of the polymer film increases. With the increase of crystallinity, a polymer film with brittleness is formed. In a polymer film with high crystallinity and brittleness, with the decrease of polymer chain mobility, when there are dissociated ions inside the polymer film, there will be a phenomenon that the ion mobility is also significantly reduced. Therefore, as described above, the general PVA film prepared by a high temperature drying process after forming a coating film exhibits properties that are not suitable for use as a polymer solid electrolyte for lithium secondary batteries.
[0008] In order to overcome these limitations of conventional polymer solid electrolytes, a technology has been developed to increase the mobility of polymer chains and improve the ionic conductivity of polymer solid electrolytes by adding plasticizers to crystalline polymers or semi-crystalline polymers. However, when a plasticizer is used, it may be difficult to set the process conditions because appropriate dispersibility and solubility (miscibility) between the polymer and the plasticizer must be ensured. In addition, when a liquid plasticizer is applied, the compatibility with the polymer is reduced, and it may be difficult to carry out the preparation process of the polymer solid electrolyte.
[0009] Therefore, there is a need to develop a technology that can improve the ionic conductivity of polymer solid electrolytes without additional additives such as plasticizers.
[0010] [Prior art literature]
[0011] [Patent Document]
[0012] (Patent Document 1) China Patent Publication No. 112259788 Summary of the invention
[0013] Technical issues
[0014] An object of the present invention is to provide a polymer solid electrolyte having improved ionic conductivity.
[0015] Another object of the present invention is to provide a method for preparing a polymer solid electrolyte having improved ionic conductivity.
[0016] Still another object of the present invention is to provide an all-solid-state battery comprising a polymer solid electrolyte having improved ionic conductivity.
[0017] Technical Solution
[0018] In order to achieve the above objectives,
[0019] The present invention provides a polymer solid electrolyte, comprising: a polymer containing a cross-linkable functional group (side chain); a lithium salt; and a solvent containing a first solvent and a second solvent, wherein the polymer solid electrolyte comprises a cross-linked structure and an amorphous polymer chain containing a cross-linkable functional group, and the cross-linked structure comprises (a) cross-linkages between the cross-linkable functional groups, (b) cross-linkages between the cross-linkable functional groups and the first solvent, and (c) bonds between the cross-linkable functional groups and the lithium salt.
[0020] The present invention also provides a method for preparing a polymer solid electrolyte, which includes the following steps: (S1) preparing a solution for forming a polymer solid electrolyte by adding a lithium salt to a solution including a polymer containing a cross-linkable functional group and a first solvent; (S2) forming a coating film by coating the solution for forming a polymer solid electrolyte on a substrate; (S3) preparing a first polymer solid electrolyte by freezing and thawing the coating film to form a cross-linked structure of a polymer containing a cross-linkable functional group, wherein the cross-linked structure of the polymer includes a lithium salt and a first solvent; and (S4) exchanging the first solvent in the first polymer solid electrolyte with a second solvent to prepare a second polymer solid electrolyte.
[0021] The present invention also provides an all-solid-state battery, which comprises the polymer solid electrolyte.
[0022] Beneficial Effects
[0023] The polymer solid electrolyte of the present invention has a cross-linked structure formed by a cross-linkable functional group contained in the polymer and a structure including an amorphous polymer chain, so the crystallinity of the polymer is reduced, and thus the ion conductivity can be improved.
[0024] In addition, due to the above structural features, polymer solid electrolytes exhibit physical properties of reduced brittleness, increased ductility and viscosity.
[0025] In addition, the ionic conductivity of PSEs can be improved by solvent exchange. DETAILED DESCRIPTION
[0026] Hereinafter, the present invention will be described in more detail to help understanding of the present invention.
[0027] The terms and words used in the present specification and claims should not be construed as limited to common or dictionary terms, but should be interpreted with meanings and concepts consistent with the technical ideas of the present invention based on the principle that the inventor can appropriately define the concepts of the terms to describe his invention in the best possible manner.
[0028] As used herein, the term "crosslinked structure" refers to a structure including a three-dimensional framework formed by polymer chains and an internal space of the framework. The polymer chains may be formed by crosslinking bonds including crosslinkable functional groups contained in the polymer. Since the crosslinked structure has a three-dimensional shape and has a form in which polymer chains are entangled with each other, it may also be referred to as a three-dimensional network structure.
[0029] Polymer solid electrolyte
[0030] The polymer solid electrolyte of the present invention is a polymer solid electrolyte comprising a polymer containing a cross-linkable functional group, a lithium salt, and a solvent comprising a first solvent and a second solvent, wherein the polymer solid electrolyte comprises a cross-linked structure and an amorphous polymer chain containing the cross-linkable functional group, and the cross-linked structure may include (a) cross-linked bonds between cross-linkable functional groups, (b) cross-linked bonds between the cross-linkable functional groups and the first solvent, and (c) bonds between the cross-linkable functional groups and the lithium salt.
[0031] In the present invention, (a) the cross-linking bond between the cross-linkable functional groups may include a hydrogen bond between the cross-linkable functional groups, and for example, the hydrogen bond may be a hydrogen bond between OH-groups.
[0032] If the cross-linked structure is formed only by the cross-linking bonds between (a) cross-linkable functional groups, the polymer solid electrolyte may develop crystallinity, and thus the ion conductivity may be reduced.
[0033] However, since the cross-linked structure includes not only (a) cross-linked bonds between cross-linkable functional groups, but also (b) cross-linked bonds between the cross-linkable functional groups and the first solvent, and (c) bonds between the cross-linkable functional groups and the lithium salt, the polymer solid electrolyte can be prevented from generating crystallinity.
[0034] In the present invention, the cross-linking bond between the (b) cross-linkable functional group and the first solvent may include a hydrogen bond, for example, the hydrogen bond may be a hydrogen bond between OH- and H+. In this case, H+ may be derived from the water solvent.
[0035] (b) The cross-linked bond between the cross-linkable functional group and the first solvent may refer to a hydrogen bond between a portion of the solvent remaining during the freezing and thawing process and the cross-linkable functional group.
[0036] In addition, the cross-linking bonds between the (b) cross-linkable functional groups and the first solvent interfere with the cross-linking bonds between the (a) cross-linkable functional groups, so that the cross-linking structure is not composed only of the cross-linking bonds between the (a) cross-linkable functional groups, and thus the crystallinity of the polymer solid electrolyte can be prevented from increasing.
[0037] In the present invention, the bond between the (c) cross-linkable functional group and the lithium salt may include a bond through Lewis acid-base interaction, and for example, the bond may be a bond between OH- and Li+.
[0038] (c) The bond between the cross-linkable functional group and the lithium salt is a bond through Lewis acid-base interaction, and may be a type of bond such as a metal-ligand bond.
[0039] In addition, the bond between the (c) cross-linkable functional group and the lithium salt interferes with the cross-linking bond between the (a) cross-linkable functional groups and the cross-linking bond between the (b) cross-linkable functional group and the first solvent, so that the cross-linking structure is not composed only of the cross-linking bond between the (a) cross-linkable functional groups, and thus the polymer solid electrolyte can be prevented from generating crystallinity, while the formation of amorphous polymer chains can be promoted. With the formation of amorphous polymer chains, the mobility of the polymer chains is improved, so the jumping effect of lithium ions is increased, so that the ionic conductivity of the polymer solid electrolyte can be improved.
[0040] In the present invention, an amorphous polymer chain may also be formed in the freezing process described later, and refers to a polymer chain that does not form a crystal by regular folding of the polymer chain but exists in a free behavior state. That is, the amorphous polymer chain may include a polymer containing a crosslinkable functional group that does not form a bond as in (a), (b), and (c).
[0041] Due to the cross-linked structure, the polymer solid electrolyte is not easily broken or damaged, and thus can stably function as a support for the electrolyte containing lithium ions.
[0042] In addition, due to the amorphous polymer chains, the polymer solid electrolyte exhibits elasticity, so that brittleness (which is a property of being easily broken) can be minimized, and due to the excellent mobility of the polymer chains, the mobility of lithium ions inside the electrolyte is improved, so that a polymer solid electrolyte with improved ionic conductivity can be provided.
[0043] In the present invention, the crosslinkable functional group contained in the polymer containing a crosslinkable functional group may have a property of being able to form a crosslinked structure by forming a bond as in (a), (b), and (c) described above.
[0044] For example, the cross-linkable functional group may include one or more selected from the group consisting of a hydroxyl group, a carboxyl group, and an amide group.
[0045] In addition, the weight average molecular weight (Mw) of the polymer comprising a crosslinkable functional group can be 80,000 g / mol to 130,000 g / mol, and specifically, can be 80,000 g / mol or more, 83,000 g / mol or more, or 85,000 g / mol or more, and 90,000 g / mol or less, 110,000 g / mol or less, or 130,000 g / mol or less. If the weight average molecular weight (Mw) of the polymer comprising a crosslinkable functional group is less than 80,000 g / mol, the bond of the crosslinkable functional group may not be fully formed to obtain a crosslinked structure. If the weight average molecular weight (Mw) of the polymer comprising a crosslinkable functional group exceeds 130,000 g / mol, the entanglement of the polymer chain in the polymer solution used in the preparation process increases, and the permeability of the solvent into the polymer chain decreases. Therefore, gelation of the polymer is accelerated, so the solubility of the polymer is reduced, and bonding of the cross-linkable functional group does not proceed smoothly, so formation of a cross-linked structure may not be easy.
[0046] In addition, the polymer containing a cross-linkable functional group may have the following characteristics: since the phase separation between the polymer and the solvent proceeds smoothly in the polymer solution used in the preparation process, the cross-linkable functional group contained in the phase-separated polymer can well form bonds (a), (b) and (c) when frozen.
[0047] For example, the polymer containing a cross-linkable functional group may include at least one selected from the group consisting of polyvinyl alcohol (PVA), gelatin, methylcellulose, agar, dextran, poly(vinyl pyrrolidone), poly(acrylamide), poly(acrylic acid) (PAA), starch-carboxymethylcellulose, hyaluronic acid-methylcellulose, chitosan, poly(N-isopropylacrylamide) and amino-terminated polyethylene glycol (amino-terminated PEG). Preferably, the polymer containing a cross-linkable functional group may be PVA, and in the preparation process of the polymer solid electrolyte, the PVA may be effectively phase-separated from the solvent when frozen, and it may be advantageous to form a cross-linked structure through bonds (a), (b) and (c) derived from the cross-linkable functional groups of the PVA phase-separated from the solvent.
[0048] In the present invention, the lithium salt is contained in the internal space of the cross-linked structure in a dissociated state, thereby improving the ion conductivity of the polymer solid electrolyte.
[0049] In addition, the lithium salt may form (c) a bond between the cross-linkable functional group and the lithium salt, thereby preventing the polymer solid electrolyte from generating crystallinity while promoting the formation of an amorphous polymer chain.
[0050] The lithium salt may include a 3 SO 2 ) 2NLi (Lithium bis(trifluoromethanesulfonyl)imide, LiTFSI), (FSO 2 ) 2 NLi (lithium bis(fluorosulfonyl)imide, LiFSI), LiNO 3 , LiOH, LiCl, LiBr, LiI, LiClO 4 , LiBF 4 , LiB 10 Cl 10 、LiPF 6 、LiCF 3 SO 3 、LiCF 3 CO 2 、LiAsF 6 、LiSbF 6 、LiAlCl 4 , CH 3 SO 3 Li, CF 3 SO 3 Li, LiSCN and LiC(CF 3 SO 2 ) 3 At least one of the group consisting of.
[0051] In the present invention, the molar ratio ([Li] / [G]) between the crosslinkable functional group ([G]) of the polymer containing the crosslinkable functional group and the lithium ([Li]) of the lithium salt contained in the polymer solid electrolyte may exceed 0.1 and be less than 0.5, and specifically may exceed 0.1, 0.2 or more, or 0.3 or more, and may be 0.4 or less, or 0.5 or less. If the molar ratio ([Li] / [G]) is less than 0.1, the ionic conductivity of the polymer solid electrolyte may decrease as the content of the lithium salt decreases. If the molar ratio ([Li] / [G]) is more than 0.5, the content of the polymer containing the crosslinkable functional group decreases, so that bonds (a), (b) and (c) may not be fully formed, and thus the crystallinity may increase and the ionic conductivity may decrease. If the crosslinkable functional group is a hydroxyl group (OH-), [G] may be expressed as [OH] or [O].
[0052] In one embodiment of the present invention, the solvent is contained inside the cross-linked structure formed by physical cross-linking of the polymer solid electrolyte, so that the solvent exchange process is easy to perform, thereby improving the ionic conductivity of the polymer solid electrolyte.
[0053] The solvent may include a first solvent and a second solvent.
[0054] The first solvent and the second solvent are different solvents from each other and may have different solubility for the polymer including a cross-linkable functional group.
[0055] The first solvent has a high solubility for the polymer containing the crosslinkable functional group and can form a crosslinked structure with the polymer containing the crosslinkable functional group. On the other hand, since the second solvent has a low solubility for the polymer containing the crosslinkable functional group, it is difficult to form a crosslinked structure with the polymer containing the crosslinkable functional group.
[0056] In addition, the first solvent and the second solvent may be solvents classified into an aqueous electrolyte solution or a non-aqueous electrolyte solution according to the structure of the battery.
[0057] In addition, the first solvent and the second solvent may be solvents different from each other according to the flame retardant electrolyte solution.
[0058] The first solvent may be any one selected from the group consisting of water, ethanol, isopropanol, dimethyl sulfoxide, acetonitrile, NMP, a co-solvent obtained by mixing water and alcohol, and a co-solvent obtained by mixing water and dimethyl sulfoxide.
[0059] The boiling point of the first solvent may be below 150° C. The boiling point of the first solvent may be lower than the boiling point of the second solvent. If the boiling point of the first solvent exceeds 150° C., the hydrogen bonds and Lewis acid-base interactions formed inside the polymer may be destroyed during the removal of the first solvent, and thus the mechanical properties of the polymer solid electrolyte may be greatly deteriorated.
[0060] The first solvent can form a cross-linked structure through a freeze / thaw process after dissolving the polymer containing a cross-linkable functional group. For example, if the first solvent is water, phase separation from the polymer containing a cross-linkable functional group obviously occurs during the freezing process, and an ice phase and a phase rich in the polymer containing a cross-linkable functional group can be formed.
[0061] The purpose of replacing the first solvent with a second solvent is to use the polymer solid electrolyte of the present invention in a battery chemistry that is susceptible to water. For example, if water is used as the first solvent, there is no problem in a battery chemistry that does not show performance degradation due to an aqueous electrolyte, but in a battery chemistry that is susceptible to water, there is a problem of deterioration of the performance of the battery or the battery not being able to work. In order to solve this problem, a polymer solid electrolyte that can stably operate a battery by removing the first solvent and replacing the first solvent with a second solvent that is available inside the battery without losing ionic conductivity can be provided.
[0062] In addition, if the first solvent is used, there is no problem in the preparation of the solid electrolyte, but there may be a problem that the solvent is easily burned in the event of a fire or explosion in the battery, thereby causing greater damage. In order to solve this problem, a polymer solid electrolyte capable of stably operating a battery by removing the first solvent and replacing the first solvent with a second solvent having flame retardant properties can be provided.
[0063] In addition, if the first solvent is used, there is no problem in the preparation of the solid electrolyte, but when the first solvent is applied as an electrolyte inside the battery, there may be a problem of reducing the product life due to undesirable side reactions and decomposition of the solvent during battery operation. In order to solve this problem, a polymer solid electrolyte capable of stably operating a battery by removing the first solvent and replacing the first solvent with a second solvent (which is stable in side reactions with the solvent) can be provided.
[0064] The second solvent may include at least one selected from the group consisting of ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), ethylene carbonate (EC), propylene carbonate (PC), vinylene carbonate (VC), diethyl carbonate (DEC), dimethyl carbonate (DMC), ethyl methyl carbonate (MEC), ethyl methyl carbonate (EMC), tetrahydrofuran (THF), 2-methyltetrahydrofuran (2-MeTHF), dioxolane (DOX), dimethoxyethane (DME), diethoxyethane (DEE), γ-butyrolactone (GBL), acetonitrile (AN) and sulfolane, or a combination thereof. For example, it may include EC:EMC (1:3), EC:EMC (1:1), EC:DMC:EMC:FEC (3:3:3:1), etc., but is not limited to these examples.
[0065] The content of the first solvent in the polymer solid electrolyte may be 1 to 1000 ppm. If the content of the first solvent exceeds 1000 ppm, there is a problem that the absorption of the second solvent is inhibited, thereby reducing the physical properties (such as ion conductivity) expected from the second solvent or reducing the stability of the battery.
[0066] In the present invention, the polymer solid electrolyte may be in the form of a self-supporting film or a coating. A self-supporting film refers to a film that can maintain a film shape by itself without a separate support at room temperature and pressure. A coating refers to a layer obtained by coating on a substrate. If the polymer solid electrolyte is in the form of a coating, the coating may be in the form of a layer coated on an electrode.
[0067] The self-standing film or coating exhibits elasticity to minimize brittleness and has characteristics as a support that stably contains lithium ions, and thus it may be a suitable form of a polymer solid electrolyte.
[0068] In the present invention, the ionic conductivity of the polymer solid electrolyte can be 10 -4 S / cm or more.
[0069] Due to the structural features including the cross-linked structure as described above, the polymer solid electrolyte has lower crystallinity and improved ionic conductivity. Therefore, despite being a solid electrolyte, it can improve the performance of all-solid-state batteries by exhibiting ionic conductivity comparable to or higher than that of conventional liquid electrolytes.
[0070] Preparation method of polymer solid electrolyte
[0071] The method for preparing a polymer solid electrolyte according to an embodiment of the present invention may include the following steps:
[0072] (S1) preparing a polymer solid electrolyte-forming solution by adding a lithium salt to a solution including a polymer including a cross-linkable functional group and a first solvent;
[0073] (S2) forming a coating film by applying the polymer solid electrolyte forming solution on a substrate;
[0074] (S3) freezing and thawing the coating film to form a cross-linked structure of a polymer containing a cross-linkable functional group, thereby preparing a first polymer solid electrolyte, wherein the cross-linked structure of the polymer includes a lithium salt and a first solvent; and
[0075] (S4) exchanging the first solvent in the first polymer solid electrolyte with a second solvent to prepare a second polymer solid electrolyte.
[0076] In the preparation method of the polymer solid electrolyte, a plasticizer for reducing the crystallinity of the polymer is not added, and through the freezing process, the crosslinking functional groups contained in the polymer induce (a) crosslinking bonds between the crosslinking functional groups, (b) crosslinking bonds between the crosslinking functional groups and the first solvent, and (c) bonds between the crosslinking functional groups and the lithium salt, so that the crystallization of the polymer can be prevented, and as a result, a polymer solid electrolyte with improved ionic conductivity can be prepared. Hereinafter, the preparation method of the polymer solid electrolyte of the present invention will be described in detail for each step.
[0077] In one embodiment of the present invention, in step (S1), a polymer solid electrolyte-forming solution may be prepared by adding a lithium salt to a solution including a polymer including a cross-linkable functional group and a first solvent.
[0078] The polymer, the first solvent and the lithium salt are as described above.
[0079] The concentration of the polymer solution containing crosslinkable functional groups can be appropriately adjusted to take into account the extent to which the coating process can proceed smoothly when the polymer solid electrolyte forming solution is applied to the substrate. For example, the concentration of the polymer solution containing crosslinkable functional groups can be 5% to 20%, and specifically can be 5% or more, 7% or more, or 9% or more, and can be 13% or less, 17% or less, or 20% or less. If the concentration of the polymer solution containing crosslinkable functional groups is less than 5%, the concentration is too dilute, so when applied to the substrate, it may flow downward. If the concentration of the polymer solution containing crosslinkable functional groups exceeds 20%, it is difficult to dissolve the lithium salt in the polymer solution at the desired concentration, and it may be difficult to apply it in the form of a uniform film due to its high viscosity.
[0080] In one embodiment of the present invention, in the above step (S2), the coating film may be formed by applying a polymer solid electrolyte-forming solution on the substrate.
[0081] The substrate is not particularly limited as long as it can be used as a support on which a polymer solid electrolyte forming solution is applied. For example, the substrate can be stainless steel (SS), polyethylene terephthalate film, polytetrafluoroethylene film, polyethylene film, polypropylene film, polybutylene film, polybutadiene film, vinyl chloride copolymer film, polyurethane film, ethylene-vinyl acetate film, ethylene-propylene copolymer film, ethylene-ethyl acrylate copolymer film, ethylene-methyl acrylate copolymer film or polyimide film.
[0082] In addition, the coating method is not particularly limited as long as it is a method that can coat the polymer solid electrolyte forming solution on the substrate in the form of a film. For example, the coating method may be rod coating, roller coating, spin coating, slit coating, die coating, blade coating, comma coating, slot die coating, lip coating or solution casting.
[0083] In one embodiment of the present invention, in step (S3), the first polymer solid electrolyte may be prepared by freezing and thawing the coating film to form a cross-linked structure of a polymer containing a cross-linkable functional group, wherein the cross-linked structure of the polymer includes a lithium salt and a first solvent.
[0084] During the freezing process, the polymer and water contained in the aqueous solution of the polymer containing crosslinkable functional groups for forming the coating film can be phase separated. Since the hydrogen bond strength between water molecules is stronger than the hydrogen bond strength between the crosslinkable functional groups and the water molecules, phase separation can be induced. The water molecules gathered by the hydrogen bonds between the water molecules exist in the ice phase through the freezing process. As a result, the number of crosslinkable functional groups that form hydrogen bonds by interacting with water molecules is significantly reduced.
[0085] Due to phase separation, the interior of the coating film is divided into (i) a polymer-poor phase and (ii) a polymer-rich phase.
[0086] (i) The polymer-poor phase is a portion including water molecules aggregated by hydrogen bonds between the water molecules and exists as an ice phase, which may also be referred to as a free water state.
[0087] (ii) The polymer-rich phase is a portion including polymers separated from the aqueous phase. The phase-separated polymer is a polymer containing a cross-linkable functional group that is free from the interaction with water molecules and is in a free state after phase separation, and does not form crystals through regular folding, but exists in an amorphous state that behaves relatively freely, which is called an amorphous polymer chain.
[0088] In addition, some cross-linkable functional groups contained in the phase-separated polymer form local crystallites. The local crystallites serve as cross-linkable connection points to form a cross-linked structure including the above-mentioned bonds (a), (b) and (c).
[0089] In addition, during the thawing process after the freezing process, ice contained in the (i) polymer-poor phase melts and evaporates, and thus a polymer solid electrolyte having an increased free volume can be prepared.
[0090] In addition, freezing can be carried out by appropriately selecting conditions sufficient to freeze the coating. For example, freezing can be carried out at a temperature of -30°C to -10°C, and specifically, the freezing temperature can be above -30°C, above -25°C, or above -23°C, and can be below -18°C, below -15°C, or below -10°C. If the freezing temperature is less than -30°C, cracks may appear in the coating. If the freezing temperature exceeds -10°C, it may be difficult to form an amorphous polymer chain region because sufficient phase separation is not achieved between the polymer and water. In addition, sufficient freezing time within the range of 20 hours to 30 hours can be considered for freezing.
[0091] In addition, thawing can be carried out by appropriately selecting conditions that can thaw to the extent that the frozen coating can be used as a polymer solid electrolyte. For example, the thawing temperature can be 15°C to 35°C, or it can be room temperature (25°C). If the thawing temperature is lower than 15°C, the water drying efficiency may decrease after thawing (ice melting). If the thawing temperature exceeds 35°C, the coating may shrink and thus cause wrinkles or warping.
[0092] As described above, bonding of (a), (b), and (c) is induced by the freezing and thawing process to form a cross-linked structure and an amorphous polymer chain.
[0093] Therefore, the formation degree of cross-linked structure can be controlled according to the number of times of freezing and thawing process. When the process of thawing process is referred to as a cycle after freezing process, freezing and thawing process can be carried out more than 1 cycle, more than 2 cycles, more than 3 cycles or more than 5 cycles. The upper limit of cycle is not particularly limited, but can be less than 10 cycles, less than 13 cycles or less than 15 cycles. Within the above range, as the number of cycles of freezing and thawing process increases, more cross-linked structures can be formed, so the modulus and the intensity of polymer solid electrolyte can increase.
[0094] In one embodiment of the present invention, in step (S4), the second polymer solid electrolyte may be prepared by exchanging the first solvent in the first polymer solid electrolyte with the second solvent.
[0095] The first solvent and the second solvent are as described above.
[0096] Solvent exchange refers to removing the first solvent in the first polymer solid electrolyte and exchanging it so that the second solvent is mainly present. The second polymer solid electrolyte containing the second solvent can be prepared by solvent exchange as described above.
[0097] In the solvent exchange, the first solvent contained in the first polymer solid electrolyte can be dried at a high temperature, and can be immersed in a second solvent to exchange the first solvent with the second solvent. More specifically, the first polymer solid electrolyte containing the first solvent can be placed in a vacuum oven, dried at a low temperature (50°C) for 6 hours, then dried at a high temperature (100°C) for 12 hours, and then the first solid electrolyte dried in the drying chamber environment is immersed in the second solvent at room temperature for 24 hours, thereby exchanging the first solvent with the second solvent.
[0098] All-solid-state battery
[0099] The present invention also relates to an all-solid-state battery including a polymer solid electrolyte, wherein the all-solid-state battery includes a negative electrode, a positive electrode, and a polymer solid electrolyte between the negative electrode and the positive electrode, and the solid electrolyte has the above-mentioned characteristics.
[0100] Specifically, polymer solid electrolytes may be suitable as electrolytes for all-solid-state batteries because physical cross-linking is formed through a freezing and thawing process, and thus crystallinity is reduced, and ionic conductivity is improved through a solvent exchange process.
[0101] In the present invention, the positive electrode included in the all-solid-state battery includes a positive electrode active material layer, and the positive electrode active material layer may be formed on one surface of a positive electrode collector.
[0102] The positive electrode active material layer includes a positive electrode active material, a binder, and a conductive material.
[0103] In addition, the positive electrode active material is not particularly limited as long as it is a material that can reversibly insert and extract lithium ions, and can be, for example, but not limited to, a layered compound or a compound substituted with one or more transition metals, such as lithium cobalt oxide (LiCoO 2 ), lithium nickel oxide (LiNiO 2 ), Li[Ni x Co y Mn z M v ]O 2 (wherein M is any one or more elements selected from the group consisting of Al, Ga and In; 0.3≤x<1.0, 0≤y, z≤0.5, 0≤v≤0.1, x+y+z+v=1), Li (Li a M b-a-b' M' b' ) 2-c A c (wherein, 0≤a≤0.2, 0.6≤b≤1, 0≤b'≤0.2, 0≤c≤0.2; M includes Mn and at least one selected from the group consisting of Ni, Co, Fe, Cr, V, Cu, Zn and Ti; M' is at least one selected from the group consisting of Al, Mg and B, and A is at least one selected from the group consisting of P, F, S and N); lithium manganese oxide, such as formula Li 1+y Mn 2-y O 4 (wherein y is 0 to 0.33), LiMnO 3 、LiMn 2 O 3 、LiMnO 2 ; Lithium copper oxide (Li 2 CuO 2 ); Vanadium oxides, such as LiV 3 O 8 、LiFe 3 O 4 、V 2 O 5 , Cu 2 V 2 O 7 Formula LiNi 1-y MyO 2 (wherein M = Co, Mn, Al, Cu, Fe, Mg, B or Ga, y = 0.01 to 0.3) represented by Ni-type lithium nickel oxide; formula LiMn 2-y M y O 2 (wherein M = Co, Ni, Fe, Cr, Zn or Ta, y = 0.01 to 0.1) or Li2 Mn 3 MO 8 (wherein M = Fe, Co, Ni, Cu or Zn) represented by a lithium manganese composite oxide; wherein a portion of Li in the formula is replaced by alkaline earth metal ions LiMn 2 O 4 ; disulfide; and Fe 2 (MoO 4 ) 3 .
[0104] In addition, based on the total weight of the positive electrode active material layer, the content of the positive electrode active material may be 40 to 80 weight %. Specifically, the content of the positive electrode active material may be 40 weight % or more or 50 weight % or more, and may be 70 weight % or less or 80 weight % or less. If the content of the positive electrode active material is less than 40 weight %, the connectivity between the wet positive electrode active material layer and the dry positive electrode active material layer may be insufficient. If the content of the positive electrode active material exceeds 80 weight %, the mass transfer resistance may increase.
[0105] In addition, the binder is a component that facilitates bonding between the positive electrode active material and the conductive material and facilitates bonding with the current collector. The binder may include at least one selected from the group consisting of styrene-butadiene rubber, acrylated styrene-butadiene rubber, acrylonitrile copolymer, acrylonitrile-butadiene rubber, nitrile rubber, acrylonitrile-styrene-butadiene copolymer, acrylic rubber, butyl rubber, fluororubber, polytetrafluoroethylene, polyethylene, polypropylene, ethylene / propylene copolymer, polybutadiene, polyethylene oxide, chlorosulfonated polyethylene, polyvinyl pyrrolidone, polyvinyl pyridine, polyvinyl alcohol, polyvinyl acetate, polyepichlorohydrin, polyphosphazene, polyacrylonitrile, polystyrene, latex, acrylic resin, phenolic resin, epoxy resin, carboxymethyl cellulose, hydroxypropyl cellulose, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, cyanoethyl cellulose, cyanoethyl sucrose, polyester, polyamide, polyether, polyimide, polycarboxylate, polycarboxylic acid, polyacrylic acid, polyacrylate, lithium polyacrylate, polymethacrylic acid, polymethacrylate, polyacrylamide, polyurethane, polyvinylidene fluoride and poly(vinylidene fluoride)-hexafluoropropylene. Preferably, the binder may include at least one selected from the group consisting of styrene-butadiene rubber, polytetrafluoroethylene, carboxymethyl cellulose, polyacrylic acid, lithium polyacrylate, and polyvinylidene fluoride.
[0106] In addition, based on the total weight of the positive electrode active material layer, the content of the binder may be 1 wt % to 30 wt %, and specifically, the content of the binder may be 1 wt % or more or 3 wt % or more, and may be 15 wt % or less or 30 wt % or less. If the content of the binder is less than 1 wt %, the adhesion between the positive electrode active material and the positive electrode current collector may be reduced. If the content of the binder exceeds 30 wt %, the adhesion is improved, but the content of the positive electrode active material is reduced accordingly, so the capacity of the battery may be reduced.
[0107] In addition, the conductive material is not particularly limited as long as it prevents side reactions in the internal environment of the all-solid-state battery and has excellent conductivity without causing chemical changes in the battery. The conductive material can generally be graphite or conductive carbon, and for example, as the conductive material, the following materials can be used alone or in combination of two or more thereof: graphite, such as natural graphite, artificial graphite; carbon black, such as carbon black, acetylene black, Ketjen black, Denka black, thermal black, channel black, furnace black, lamp black, thermal black; a carbon-based material whose crystal structure is graphene or graphite; conductive fibers, such as carbon fibers and metal fibers; fluorocarbons; metal powders, such as aluminum powder and nickel powder; conductive whiskers, such as zinc oxide and potassium titanate; conductive oxides, such as titanium oxide; and conductive polymers such as polyphenylene derivatives, but not necessarily limited thereto.
[0108] Based on the total weight of the positive electrode active material layer, the content of the conductive material may generally be 0.5 wt % to 30 wt %, and specifically, the content of the conductive material may be 0.5 wt % or more or 1 wt % or more, and may be 20 wt % or less or 30 wt % or less. If the content of the conductive material is too small, i.e., less than 0.5 wt %, it is difficult to expect the effect of improving conductivity or the electrochemical performance of the battery may deteriorate. If the content of the conductive material exceeds 30 wt % and is therefore too large, the amount of the positive electrode active material may be relatively small, so that the capacity and energy density may be reduced. The method of incorporating the conductive material into the positive electrode is not particularly limited, and conventional methods known in the art may be used, such as coating on the positive electrode active material.
[0109] In addition, the positive electrode current collector supports the positive electrode active material layer and serves to transfer electrons between the external wire and the positive electrode active material layer.
[0110] There is no particular limitation on the positive electrode current collector, as long as it has high conductivity and does not cause chemical changes in the all-solid-state battery. For example, as the positive electrode current collector, copper, stainless steel, aluminum, nickel, titanium, palladium, sintered carbon; copper or stainless steel surface-treated with carbon, nickel, silver, etc.; aluminum-cadmium alloy, etc. can be used.
[0111] In order to enhance the bonding force with the positive electrode active material layer, the positive electrode collector may have a fine irregular structure or a three-dimensional porous structure on the surface of the positive electrode collector. Therefore, the positive electrode collector may include various forms such as a film, a sheet, a foil, a mesh, a net, a porous body, a foam, and a non-woven fabric.
[0112] The positive electrode as described above can be prepared by conventional methods, specifically, the positive electrode is manufactured by the following process: the positive electrode active material layer formation composition prepared by mixing the positive electrode active material, the conductive material and the binder in the organic solvent is applied to the positive electrode current collector and dried, and optionally compressed and formed onto the current collector to increase the electrode density. At this time, as an organic solvent, it is preferred to use an organic solvent that can evenly disperse the positive electrode active material, the binder and the conductive material and easily evaporate. Specifically, acetonitrile, methanol, ethanol, tetrahydrofuran, water and isopropanol can be cited.
[0113] In the present invention, the negative electrode included in the all-solid-state battery includes a negative electrode active material layer, and the negative electrode active material layer may be formed on one surface of a negative electrode current collector.
[0114] The negative electrode active material can be a material that can reversibly insert or release lithium ions (Li + ), a material capable of reacting with lithium ions to reversibly form a lithium-containing compound, lithium metal or a lithium alloy.
[0115] Able to reversibly insert or deintercalate lithium ions (Li + ) can be, for example, crystalline carbon, amorphous carbon or a mixture thereof. + ) to reversibly form a lithium-containing compound may be, for example, tin oxide, titanium nitrate, or silicon. The lithium alloy may be, for example, an alloy of lithium (Li) and a metal selected from the group consisting of sodium (Na), potassium (K), rubidium (Rb), cesium (Cs), francium (Fr), beryllium (Be), magnesium (Mg), calcium (Ca), strontium (Sr), barium (Ba), radium (Ra), aluminum (Al), and tin (Sn).
[0116] Preferably, the negative electrode active material may be lithium metal, and specifically, may be in the form of a lithium metal thin film or lithium metal powder.
[0117] Based on the total weight of the negative electrode active material layer, the content of the negative electrode active material may be 40 to 80 weight %. Specifically, the content of the negative electrode active material may be 40 weight % or more or 50 weight % or more, and may be 70 weight % or less or 80 weight % or less. If the content of the negative electrode active material is less than 40 weight %, the connectivity between the wet negative electrode active material layer and the dry negative electrode active material layer may be insufficient. If the content of the negative electrode active material exceeds 80 weight %, the mass transfer resistance may increase.
[0118] In addition, the binder is the same as described above in the positive electrode active material layer.
[0119] In addition, the conductive material is the same as described in the above-mentioned positive electrode active material layer.
[0120] In addition, the negative electrode current collector is not particularly limited as long as it has conductivity without causing chemical changes in the battery, and for example, the negative electrode current collector may be copper, stainless steel, aluminum, nickel, titanium, sintered carbon; copper or stainless steel surface-treated with carbon, nickel, titanium, silver, etc.; or aluminum-cadmium alloy. In addition, as in the positive electrode current collector, the negative electrode current collector may be used in various forms, such as a film, sheet, foil, net, porous body, foam, and non-woven fabric having fine irregularities on its surface.
[0121] The manufacturing method of the negative electrode is not particularly limited, and can be manufactured by forming a negative electrode active material layer on the negative electrode current collector using a layer or film formation method commonly used in the art. For example, methods such as pressing, coating or vapor deposition can be used. Moreover, the case where a metal lithium film is formed on a metal plate by initial charging after assembling a battery without a lithium film on the negative electrode current collector is also included in the negative electrode of the present invention.
[0122] In addition, the present invention provides a battery module including the all-solid-state battery as a unit cell, a battery pack including the battery module, and a device including the battery pack as a power source.
[0123] In this case, examples of the above-mentioned devices may include, but are not limited to: electric tools driven by electric motors; electric vehicles, including electric vehicles (EV), hybrid electric vehicles (HEV) and plug-in hybrid electric vehicles (PHEV), etc.; electric motorcycles, including electric bicycles (E-bikes) and electric scooters (E-scooters); electric golf carts; and power storage systems. In the following, preferred embodiments are given to help understand the present invention, but the following embodiments are only illustrative of the present invention, and it will be obvious to those skilled in the art that various changes and modifications can be made within the scope and technical concept of the present invention, and such changes and modifications are naturally also within the scope of the appended claims.
[0124] Example
[0125] Hereinafter, preferred embodiments are given to help understand the present invention, but the following embodiments are provided only to facilitate understanding of the present invention, and the present invention is not limited thereto.
[0126] In the following Examples and Comparative Examples, polymer solid electrolytes including a polymer including a cross-linkable functional group, a lithium salt, and a solvent as described in the following Table 1 were prepared.
[0127] Table 1:
[0128]
[0129] <Example>
[0130] Example 1: Preparation of polymer solid electrolyte
[0131] PVA (Mw: 89,000 g / mol; degree of hydrolysis: >99%) was mixed with water to prepare a 10% PVA aqueous solution. LiTFSI was added to the PVA aqueous solution and then stirred to prepare a solution containing PVA as a polymer having a crosslinkable functional group and LiTFSI as a lithium salt. At this time, the molar ratio ([Li] / [O]) of "O" contained in the crosslinkable functional group of PVA to "Li" contained in the lithium salt was set to 0.1.
[0132] The solution was coated on a SS foil as a substrate by a bar coating method to form a coating film, and then, it was frozen at -20°C for 24 hours and thawed at 25°C to prepare a polymer solid electrolyte.
[0133] Example 2
[0134] A polymer solid electrolyte was prepared in the same manner as in Example 1, except that the molar ratio ([Li] / [O]) of “O” contained in the cross-linkable functional group of PVA to “Li” contained in the lithium salt was 0.4.
[0135] Example 3
[0136] A polymer solid electrolyte was prepared in the same manner as in Example 1, except that the molar ratio of "O" contained in the cross-linkable functional group of PVA to "Li" contained in the lithium salt ([Li] / [O]) was 0.4, and water (H) as the first solvent inside the prepared polymer solid electrolyte was removed. 2 O), and then ethyl methyl carbonate (EMC) was added as a second solvent to prepare a polymer solid electrolyte.
[0137] Example 4
[0138] A polymer solid electrolyte was prepared in the same manner as in Example 3, except that the second solvent was DMC.
[0139] Example 5
[0140] A polymer solid electrolyte was prepared in the same manner as in Example 3, except that the molar ratio ([Li] / [O]) of “O” contained in the crosslinkable functional group of PVA to “Li” contained in the lithium salt was 0.25, and the first solvent was DMSO.
[0141] <Comparative Example>
[0142] Comparative Example 1
[0143] A polymer solid electrolyte was prepared in the same manner as in Example 3, except that a solution including PVA as a polymer having a crosslinkable functional group and LiTFSI as a lithium salt was coated on a SS foil as a substrate and then dried at 80°C without a freezing and thawing process.
[0144] Comparative Example 2
[0145] A polymer solid electrolyte was prepared in the same manner as in Example 3, except that a solution including PVA as a polymer having a crosslinkable functional group and LiTFSI as a lithium salt was coated on a SS foil as a substrate and then dried at 25°C without a freezing and thawing process.
[0146] Comparative Example 3
[0147] A polymer solid electrolyte was prepared in the same manner as in Example 2, except that a solution including PVA as a polymer having a crosslinkable functional group mixed with EMC and LiTFSI as a lithium salt was coated on a SS foil as a substrate and then dried at 80° C. without a freezing and thawing process.
[0148] Comparative Example 4
[0149] A polymer solid electrolyte was prepared in the same manner as in Example 2, except that a PEO polymer was used instead of PVA and the PEO polymer was dissolved in acetonitrile.
[0150] Comparative Example 5
[0151] A polymer solid electrolyte was prepared in the same manner as in Example 3, except that a PEO polymer was used instead of PVA.
[0152] Comparative Example 6
[0153] A polymer solid electrolyte was prepared in the same manner as in Example 1, except that the molar ratio ([Li] / [O]) of “O” contained in the cross-linkable functional group of PVA to “Li” contained in the lithium salt was 0.5.
[0154] <Experimental example>
[0155] Experimental Example 1
[0156] In order to measure the ionic conductivity of the polymer solid electrolytes in the form of films prepared in the examples and comparative examples, the polymer solid electrolytes were punched into a size of 1.7671 cm 2The circular shape of the punched polymer solid electrolyte was placed between two sheets of stainless steel (SS) to prepare a coin cell.
[0157] The resistance was measured using an electrochemical impedance spectrometer (EIS, VM3, Bio Logic Science Instrument) at 25° C. with an amplitude of 10 mV and a scanning range of 500 KHz to 20 MHz, and then the ionic conductivity of the polymer solid electrolyte was calculated using the following equation 1.
[0158] [Equation 1]
[0159]
[0160] Wherein, σi is the ionic conductivity of the polymer solid electrolyte (S / cm), R is the resistance of the polymer solid electrolyte measured by electrochemical impedance spectroscopy (Ω), L is the thickness of the polymer solid electrolyte (μm), and A is the area of the polymer solid electrolyte (cm 2 ).
[0161] The ionic conductivity of the polymer solid electrolyte calculated using the above equation 1, the possibility of forming a self-standing film, and the results of observing the appearance of the polymer solid electrolyte are shown in the following Table 2. At this time, the possibility of forming a self-standing film (formation: ○, no formation: X) and the appearance of the polymer solid electrolyte were visually observed.
[0162] Table 2:
[0163]
[0164] As shown in Table 2 above, it was confirmed that a self-supporting film-formed polymer solid electrolyte (Examples 1 to 5) can be prepared by using PVA having a molar ratio of a crosslinkable functional group to lithium in a lithium salt ([Li] / [OH]) within an appropriate range as a polymer containing a crosslinkable functional group and applying a freezing and thawing process.
[0165] In Comparative Example 1, the electrolyte was prepared using a high temperature drying process at 80° C. and was in the form of a liquid rather than a film.
[0166] In Comparative Example 2, the electrolyte was prepared using a room temperature drying process at 25° C., and it was found that the polymer solid electrolyte had low mechanical strength and low ionic conductivity due to the absence of physical crosslinking formed by the freezing and thawing process.
[0167] In Comparative Example 3, the electrolyte was prepared using a high temperature drying process at 80°C, and a solution was prepared by adding PVA, a polymer containing a crosslinkable functional group, to an ethyl methyl carbonate (EMC) solvent, but PVA was not dissolved in the EMC solvent and was in the form of a liquid rather than a film.
[0168] In Comparative Examples 4 and 5, PEO was used as the polymer, but it was found that even if the freezing and thawing process was applied, a cross-linked structure was not formed, and thus the ion conductivity was significantly low.
[0169] Example 6
[0170] A polymer solid electrolyte was prepared in the same manner as in Example 1, except that the freezing and thawing process was performed for 2 cycles.
[0171] Example 7
[0172] A polymer solid electrolyte was prepared in the same manner as in Example 1, except that the freezing and thawing process was performed for 1 cycle.
[0173] Example 8
[0174] A polymer solid electrolyte was prepared in the same manner as in Example 1, except that the freezing and thawing process was performed for 5 cycles.
[0175] Example 9
[0176] A polymer solid electrolyte was prepared in the same manner as in Example 1, except that the freezing and thawing process was performed for 10 cycles.
[0177] Comparative Example 7
[0178] PVA (Mw: 89,000 g / mol; hydrolysis degree: >99%) was mixed with water to prepare a 10 wt % PVA aqueous solution, and the obtained aqueous solution was then coated on a SS foil and then dried at a high temperature (90° C., 3 hours) to prepare a PVA film.
[0179] Comparative Example 8
[0180] A PVA film was prepared in the same manner as in Comparative Example 9, except that boric acid was added as a cross-linking agent.
[0181] Experimental Example 2
[0182] Experiments were conducted to compare the presence or absence and the degree of formation of a cross-linked structure inside a polymer solid electrolyte.
[0183] Since only the presence or absence and the degree of formation of the cross-linked structure were compared, the PVA film of Comparative Example 7 not including the cross-linked structure and Comparative Example 8 in which a chemical cross-linked structure was formed by a cross-linking agent were used for comparison.
[0184] (1) Check the swelling degree
[0185] The sample to be tested was immersed in water at room temperature (25° C.) for 12 hours, and then the swelling degree of the sample was confirmed and determined according to the following standard.
[0186] <Standard for Determining the Degree of Swelling>
[0187] ◎: Swelled to more than 80% of the total volume.
[0188] ○: Swelled to 50% or more of the total volume.
[0189] △: Swelled to more than 20% of the total volume.
[0190] X: Swelled to less than 10% of the total volume.
[0191] (2) Modulus
[0192] The modulus was measured using a universal testing machine (UTM).
[0193] Table 3:
[0194]
[0195] With reference to Table 3, it can be seen that Examples 2 and 6 to 9 show that the polymer solid electrolyte prepared by the freezing and thawing process exhibits a modulus above a certain level, and as the number of cycles of the freezing and thawing process increases, the modulus also increases. In addition, as the number of cycles increases, the degree of swelling decreases. In general, the degree of swelling and mechanical properties of polymers are largely affected by the degree of crosslinking. The formation of crosslinking points is used to increase the internal resistance of the polymer chain, resulting in an increase in anti-swelling properties and mechanical strength. In particular, the formation of physical crosslinks based on the freeze-thaw process is affected by the number of repetitions of the freeze-thaw process. From the results that the modulus increases and the degree of swelling decreases as the number of cycles increases, it can be seen that the crosslinked structure also increases as the number of cycles increases. Although Example 1 shows that the degree of swelling is more than 50% of the total volume, as a result of measurement after 12 hours at room temperature, it is suitable for the physical properties required for polymer solid electrolytes for all-solid-state batteries.
[0196] It can be seen that the PVA film of Comparative Example 7 swells to more than 80% of the total volume, from which it can be seen that the polymer does not contain a cross-linked structure.
[0197] The PVA film of Comparative Example 8 had a chemically cross-linked structure formed by adding boric acid as a cross-linking agent, and it was found that the modulus thereof was reduced compared with Comparative Example 7 in which no cross-linked structure was formed.
[0198] The PVA film of Comparative Example 8 has a reduced modulus compared to Comparative Example 7 because the crystallinity is reduced and the flexibility of the polymer is increased with the formation of a chemically cross-linked structure.
[0199] On the other hand, unlike the preparation methods of Comparative Examples 7 and 8, Examples 2 and 6 to 9 correspond to hydrogel-type PVA films based on physical crosslinking formed using a freezing and thawing process. This shows a trend that the modulus increases with the increase of crosslinking. Examples 2 and 6 to 9 show that as the cycles of the freezing and thawing process increase, the crosslinked structure also increases, and the modulus also tends to increase. Through the freezing and thawing process, some crosslinkable functional groups contained in the PVA form local grains, and the local grains act as crosslinkable connection points to increase the modulus.
[0200] Although the present invention has been described above through limited embodiments and drawings, the present invention is not limited thereto, and it is obvious to those skilled in the art that various modifications and changes can be made within the technical spirit of the present invention and the equivalent scope of the claims to be described below.
Claims
1. A polymer solid electrolyte comprising: A polymer comprising a cross-linkable functional group; Lithium salts; and a solvent, the solvent comprising a first solvent and a second solvent, wherein the polymer solid electrolyte comprises a cross-linked structure and an amorphous polymer chain comprising the cross-linkable functional group, and The cross-linked structure includes (a) cross-linked bonds between cross-linkable functional groups, (b) cross-linked bonds between the cross-linkable functional groups and the first solvent, and (c) bonds between the cross-linkable functional groups and the lithium salt.
2. The polymer solid electrolyte according to claim 1, in: The cross-linking bonds between the (a) cross-linkable functional groups include hydrogen bonds, The cross-linking bond between the (b) cross-linkable functional group and the first solvent comprises a hydrogen bond, and The bond between the (c) cross-linkable functional group and the lithium salt includes a bond via Lewis acid-base interaction.
3. The polymer solid electrolyte according to claim 1, in, The content of the first solvent is 1 ppm to 1000 ppm.
4. The polymer solid electrolyte according to claim 1, in, The first solvent is at least one selected from the group consisting of water, ethanol, isopropanol, dimethyl sulfoxide, acetonitrile, NMP, a co-solvent obtained by mixing water and alcohol, and a co-solvent obtained by mixing water and dimethyl sulfoxide.
5. The polymer solid electrolyte according to claim 1, in, The second solvent is at least one selected from the group consisting of ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), ethylene carbonate (EC), propylene carbonate (PC), vinylene carbonate (VC), diethyl carbonate (DEC), dimethyl carbonate (DMC), ethyl methyl carbonate (MEC), ethyl methyl carbonate (EMC), tetrahydrofuran (THF), 2-methyltetrahydrofuran (2-MeTHF), dioxolane (DOX), dimethoxyethane (DME), diethoxyethane (DEE), γ-butyrolactone (GBL), acetonitrile (AN) and sulfolane.
6. The polymer solid electrolyte according to claim 1, in, The cross-linkable functional group includes at least one selected from the group consisting of a hydroxyl group, a carboxyl group, and an amide group.
7. The polymer solid electrolyte according to claim 1, in, The polymer containing a cross-linkable functional group includes at least one selected from the group consisting of polyvinyl alcohol (PVA), gelatin, methylcellulose, agar, dextran, poly(vinyl pyrrolidone), poly(acrylamide), starch-carboxymethyl cellulose, hyaluronic acid-methyl cellulose, chitosan, poly(N-isopropylacrylamide) and amino-terminated polyethylene glycol.
8. The polymer solid electrolyte according to claim 1, wherein The molar ratio [Li] / [G] of the lithium [Li] of the lithium salt to the cross-linkable functional group [G] of the polymer is more than 0.1 and less than 0.
5.
9. The polymer solid electrolyte according to claim 1, in, The lithium salt includes (CF3SO2)2NLi (lithium bis(trifluoromethanesulfonyl)imide, LiTFSI), (FSO2)2NLi (lithium bis(fluorosulfonyl)imide, LiFSI), LiNO3, LiOH, LiCl, LiBr, LiI, LiClO4, LiBF4, LiB 10 Cl 10 , LiPF6, LiCF3SO3, LiCF3CO2, LiAsF6, LiSbF6, LiAlCl4, CH3SO3Li, CF3SO3Li, LiSCN and LiC(CF3SO2)3.
10. The polymer solid electrolyte according to claim 1, in, The polymer solid electrolyte is in the form of a free-standing film or coating.
11. The polymer solid electrolyte according to claim 1, in, The ionic conductivity of the polymer solid electrolyte is 1.0 x 10 -4 S / cm or more.
12. A method for preparing a polymer solid electrolyte, comprising the following steps: (S1) preparing a polymer solid electrolyte-forming solution by adding a lithium salt to a solution including a polymer including a cross-linkable functional group and a first solvent; (S2) forming a coating film by applying the polymer solid electrolyte forming solution on a substrate; (S3) freezing and thawing the coating film to form a cross-linked structure of a polymer containing a cross-linkable functional group, thereby preparing a first polymer solid electrolyte, wherein the cross-linked structure of the polymer includes a lithium salt and a first solvent; as well as (S4) exchanging the first solvent in the first polymer solid electrolyte with a second solvent to prepare a second polymer solid electrolyte.
13. The method for preparing a polymer solid electrolyte according to claim 12, in: The polymer solid electrolyte comprises a cross-linked structure, The cross-linked structure includes (a) cross-linked bonds between cross-linkable functional groups, (b) cross-linked bonds between the cross-linkable functional groups and the first solvent, and (c) bonds between the cross-linkable functional groups and the lithium salt. The cross-linking bonds between the (a) cross-linkable functional groups include hydrogen bonds, The cross-linking bond between the (b) cross-linkable functional group and the first solvent comprises a hydrogen bond, and The bond between the (c) cross-linkable functional group and the lithium salt includes a bond via Lewis acid-base interaction.
14. The method for preparing a polymer solid electrolyte according to claim 12, wherein: The freezing is performed at -30°C to -10°C.
15. The method for preparing a polymer solid electrolyte according to claim 12, wherein: The thawing is performed at 15°C to 35°C.
16. The method for preparing a polymer solid electrolyte according to claim 12, in, The solvent exchange is performed by drying a first solvent included in the first polymer solid electrolyte at a high temperature and then immersing in a second solvent to exchange the first solvent with the second solvent.
17. An all-solid-state battery comprising the polymer solid electrolyte according to any one of claims 1 to 11.
